Religious Education Policy in Public Schools During the New Order - Mohammad Kosim (Karsa: Journal of Social and Islamic Culture, 2020)
The new order government policy about religious education in state schools gradually led to an accommodative policy. If the old order government made religious education a facultative subject, then at the beginning of the new order the government strengthened the position of religious education by removing facultative provisions, even though they were not obligatory. Until finally, through Law number 2 (1989), the government required religious education to be taught in all channels, types, and levels of education. And the right of every student to get religious lessons by their religion and is taught by religious educators. This research includes historical research and policy studies, because it relies on past data,  whose steps consist of four main activities, namely heuristics, verification, interpretation, and historiography. This accommodative policy is influenced by several factors, including; the government’s determination to implement Pancasila purely and consistently after it was diverted in the old order era; the weakening of the government’s power at that time so that it required the political support of muslims as the majority population; There is an intellectual transformation of muslim thinkers and political activists towards harmonious and complementary political relations between Islam and the state so that Islamic ideas are more easily accepted; and muslims experience a process of rapid social, educational, economic and political mobilization and so that more and more people are involved in government and can influence policies in a pro-muslim direction.